Experience: developing an inpatient malnutrition checklist for children 6 to 59 months to improve WHO protocol adherence and facilitate quality improvement in a low-resource setting - Kathryn Beck; Angelique Mukantaganda; Scheilla Bayitondere; Richard Ndikuriyo; Almaque Dushimirimana; Vianney Bihibindi; Souzane Nyiranganji; Michel Habiyaremye; Jennifer Werdenberg (Taylor & Francis Group, 2018)
In low-resource settings, inpatient case fatality for severe acute malnutrition (SAM) remains high despite evidenced-based protocols and resources to treat SAM. Key reasons include a combination of insufficiently trained staff, poor teamwork and inadequate compliance to WHO treatment guidelines which are proven to reduce mortality. Checklists have been used in surgery and obstetrics to ameliorate similarly complicated yet repetitive work processes and may be a key strategy to improving inpatient SAM protocol adherence and reducing unnecessary death. Here, we share our experience developing and piloting an inpatient malnutrition checklist (MLNC) for children 6 to 59 months and associated scoring system to coordinate care delivery, improve team documentation, strengthen WHO malnutrition protocol adherence and facilitate quality improvement in a district hospital in rural Rwanda. MLNC was developed after careful review of the 2009 Rwandan National Nutrition Protocol and 2013 WHO malnutrition guidelines. Critical steps were harmonized, extracted and designed into an initial MLNC with input from pediatric ward nurses, doctors, a locally based pediatrician and a registered dietitian. A scoring system was developed to facilitate quality improvement. Using the standard Plan-Do-Study-Act cycle, MLNC was modified and progress assessed on a monthly to bimonthly basis. Significant modifications occurred in the first 6 months of piloting including incorporation of treatment reminders and formatting improvements, as well as initiation of the MLNC from the emergency department. The MLNC is the first checklist to be developed that unifies WHO 10 steps of treatment of inpatient SAM with local standards. Anecdotally, MLNC was observed to identify gaps in key malnutrition care, promote protocol adherence and facilitate quality improvement. Data gathering on the MLNC local facility impact is underway. Collaborative international efforts are needed to create an inpatient malnutrition checklist for wider use to improve quality and reduce unnecessary, facility-based child mortality.